Contact-FP: A Dimerization-Dependent Fluorescent Protein Toolkit for Visualizing Membrane Contact Site Dynamics - Gregory E. Miner; Sidney Y. Smith; Wendy K. Showalter; Christina M. So; Joey V. Ragusa; Alex E. Powers; Maria Clara Zanellati; Chih-Hsuan Hsu; Michelle F. Marchan; Sarah Cohen (Contact, 2024)
Membrane contact sites (MCSs) are sites of close apposition between two organelles used to exchange ions, lipids, and information. Cells respond to changing environmental or developmental conditions by modulating the number, extent, or duration of MCSs. Because of their small size and dynamic nature, tools to study the dynamics of MCSs in live cells have been limited. Dimerization-dependent fluorescent proteins (ddFPs) targeted to organelle membranes are an ideal tool for studying MCS dynamics because they reversibly interact to fluoresce specifically at the interface between two organelles. Here, we build on previous work using ddFPs as sensors to visualize the morphology and dynamics of MCSs. We engineered a suite of ddFPs called Contact-FP that targets ddFP monomers to lipid droplets (LDs), the endoplasmic reticulum (ER), mitochondria, peroxisomes, lysosomes, plasma membrane, caveolae, and the cytoplasm. We show that these probes correctly localize to their target organelles. Using LDs as a test case, we demonstrate that Contact-FP pairs specifically localize to the interface between two target organelles. Titration of LD-mitochondria ddFPs revealed that these sensors can be used at high concentrations to drive MCSs or can be titrated down to minimally perturb and visualize endogenous MCSs. We show that Contact-FP probes can be used to: (1) visualize LD-mitochondria MCS dynamics, (2) observe changes in LD-mitochondria MCS dynamics upon overexpression of PLIN5, a known LD-mitochondrial tether, and (3) visualize two MCSs that share one organelle simultaneously (e.g., LD-mitochondria and LD-ER MCSs). Contact-FP probes can be optimized to visualize MCSs between any pair of organelles represented in the toolkit.